2020
DOI: 10.1073/pnas.2010275117
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione peroxidase 8 (GPX8)/IL-6/STAT3 axis is essential in maintaining an aggressive breast cancer phenotype

Abstract: One of the emerging hallmarks of cancer illustrates the importance of metabolic reprogramming, necessary to synthesize the building blocks required to fulfill the high demands of rapidly proliferating cells. However, the proliferation-independent instructive role of metabolic enzymes in tumor plasticity is still unclear. Here, we provide evidence that glutathione peroxidase 8 (GPX8), a poorly characterized enzyme that resides in the endoplasmic reticulum, is an essential regulator of tumor aggressiveness. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 73 publications
(77 reference statements)
3
44
0
1
Order By: Relevance
“…Similar to our results, HDAC inhibitors reduced the expression of GPX8 protein in fibroblasts derived from a Niemann-Pick type C patient [29] and Gpx8 mRNA in SK-MEL-3 melanoma cells [30]. From these results, we speculated that downregulation of GPX8 may cause an increase in hydrogen peroxide and oxidative stress levels in the ER, which interrupts proper folding and maturation of secreted and membrane proteins by inducing aberrant disulfide bonds, as reported previously [31]. It is well established that HDACi hyperacetylates histones, which results in transcriptionally active euchromatin.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, HDAC inhibitors reduced the expression of GPX8 protein in fibroblasts derived from a Niemann-Pick type C patient [29] and Gpx8 mRNA in SK-MEL-3 melanoma cells [30]. From these results, we speculated that downregulation of GPX8 may cause an increase in hydrogen peroxide and oxidative stress levels in the ER, which interrupts proper folding and maturation of secreted and membrane proteins by inducing aberrant disulfide bonds, as reported previously [31]. It is well established that HDACi hyperacetylates histones, which results in transcriptionally active euchromatin.…”
Section: Discussionsupporting
confidence: 91%
“…M2 macrophage-secreted CHI3L1 could promote gastric and breast cancer metastasis [42] , and CHI3L1 modulates an immune suppressive microenvironment by reprogramming M2-like TAM in GBM [43] . TNFAIP6, RBP1, FBXO17, and GPX8 promote metastasis and invasiveness of tumor [44] , [45] , [46] , [47] . SLC43A3 and ADAM12 have been revealed as the biomarker and therapeutic target in tumor patients [48] , [49] .…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer is a major health threat to women worldwide ( 1 , 2 ). Although a number of studies have investigated the cellular and molecular mechanisms underlying the occurrence and development of breast cancer ( 31 - 33 ), early detection is hindered by the lack of effective diagnostic biomarkers. Numerous studies have indicated that lncRNAs may be used as potential therapeutic targets or prognostic markers of breast cancer ( 34 ).…”
Section: Discussionmentioning
confidence: 99%